Heterogeneous reactions of N2O5 with H2O and HCl on ice surfaces - Implications for Antarctic ozone depletion - Leu, Ming-Taun (1988)
This paper reports on the measurements of reaction probabilities for heterogeneous reaction of N2O5 with H2O and HCl on ice surfaces at 195 K, using a fast-flow reactor coupled with a quadrupole mass spectrometer. The reaction probability for N2O5 on pure-water ice was found to be 0.028 + or - 0.011, with nitric acid in the solid phase as the sole product. In the presence of HCl in ice, the probability of N2O5 reaction was enhanced (to 0.037); the reaction produced, besides solid-phase nitric acid, ClNO2 and ClONO which were released into the gas phase within a few milliseconds. The latter two compounds can be readily photolyzed in the austral spring to form active chlorine which would remove stratospheric ozone. It is suggested that, since the polar stratospheric clouds are believed to contain HCl-ice mixture on the surface, the reactions of N2O5 on H2O/HCl particles is a major factor in the Antarctic springtime ozone depletion.